Peningkatan Kapasitas Perempuan dalam Kesehatan Jiwa Keluarga Di masa Pandemi Covid-19 - Retna Tri Astuti; Lailatul Nur Hidayati; Listiana Listiana; Farihah Abghi Rusda; Rachel Pasa Vicha Abdilla (Berdikari: Jurnal Inovasi dan Penerapan Ipteks, 2021)
The Covid-19 pandemic that has occurred in the world has spread to Indonesia. Caused by the Covid-19 pandemic only on the health aspect but also on the social and economic aspects the impact not only has an impact on increasing problems. This problem is also experienced by the people of Ngapus Village. Ngapus village is a village prone to landslides. Most of the people in Ngapus Village work as farmers. The level of community education is low, namely elementary and junior high school graduates so that the income level of the community in Ngapus Village is still below the average. With the Covid-19 pandemic, it will certainly increase the poverty level in this village to a high level. Women like women in other villages also rose up and played a role in overcoming the socio-economic problems of the family. In helping to meet the needs of the family sometimes experience stress so it is necessary to make mental health efforts, especially at the family level. This program aims to help improve the mental health condition and preparedness of Ngapus Village residents. The method used to achieve this goal is through non-formal education for women, this is easier for the Dasawisma group because they are a vulnerable group. The implementation of community development is carried out through non-formal education, namely training carried out with lectures, discussions, practices and assistance to Mrs. Dasawisma, namely health about covid-19 and trauma healing due to the Covid-19 pandemic, in addition to training on making herbal drinks. The results of the implementation of this community development program are an increase in the knowledge and skills of mothers in the mental health of Dasawisma and an increase in preparedness in the field of mental, social and economic health during the Covid-19 pandemic.